1988
DOI: 10.1055/s-2007-1024983
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Physical Exercise on Peritoneal Macrophage Functions: Histochemical and Phagocytic Studies

Abstract: Peritoneal murine macrophages were assayed for their enzyme content and phagocytic activity after physical exercise. An endurance training as well as a single exhaustive exercise bout caused increased enzyme and phagocytic activities. However, a homogeneous activation could not be observed. The exhaustively exercised animals delivered macrophages with the highest levels of activation. Therefore, physical exercise has to be listed among the stimuli with macrophage-activating function. The inconsistency between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 6 publications
3
36
0
2
Order By: Relevance
“…Macrophages are an appropriate cell subset in which to study the influence of physical exercise and stress on the status of the immune system (Fehr, Lotzerich & Michna, 1988). It is important to study their non-specific immune response, because this cell population is the 'first hurdle' confronting infectious diseases within the body.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are an appropriate cell subset in which to study the influence of physical exercise and stress on the status of the immune system (Fehr, Lotzerich & Michna, 1988). It is important to study their non-specific immune response, because this cell population is the 'first hurdle' confronting infectious diseases within the body.…”
Section: Discussionmentioning
confidence: 99%
“…In general, researchers have found that the acute exercise-induced effects seen in various peritoneal macrophage functions are somewhat attenuated after exercise training of 30 or less days duration, but are still significantly different from sedentary control animals. 33,35,36 This suggests that acute exercise (especially novel strenuous exercise) is a potent stimulus for altering peritoneal macrophage activity and that chronic training may cause adaptations that diminish the acute exercise response.…”
Section: Monocyte/macrophage Functionmentioning
confidence: 99%
“…Aside from one study that found that acute exercise increased tissue macrophage chemotaxis and phagocytosis in humans, 28 most studies of exercise or stress on macrophage function have been performed using animal models obtaining macrophages from the spleen, peritoneum or alveoli. [32][33][34][35][36][37] and antitumour 11,38 activity. Our group has shown that both moderate and exhaustive treadmill running over periods of 3-7 days increases the antitumour activity of thioglycolate (TG)-elicited or P. acnes-activated peritoneal macrophages in young mice.…”
Section: Monocyte/macrophage Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same way, moderate intensity exercise training enhances immune function, whereas intense exercise training depresses the immune system (27,29). With regards to the influence of endurance training on the immune function, the results of animal experiments have shown an increase in phagocytic activity and in chemotaxis of peritoneal Ms, as well as of the proliferative response of T cells to mitogens (12,14,35,36). On the other hand, few studies have evaluated the immunomodulatory effect of exercise training on peritoneal M function, since activated Ms are important sources of pro-inflammatory factors.…”
mentioning
confidence: 81%